2005
DOI: 10.2516/ogst:2005004
|View full text |Cite
|
Sign up to set email alerts
|

Natural Geochemical Analogues for Carbon Dioxide Storage in Deep Geological Porous Reservoirs, a United Kingdom Perspective

Abstract: Résumé -Analogues géochimiques naturels pour le stockage du dioxyde de carbone en réservoir géologique poreux profond : perspective pour le Royaume-Uni -La concentration élevée en CO 2 atmosphérique participe au réchauffement climatique. Une mesure d'atténuation consiste à capter le CO 2 émis par les centrales électriques qui utilisent des combustibles fossiles, et à le stocker dans des aquifères salins ou dans des gisements exploités d'hydrocarbures. Des projets de démonstration déjà en cours et des analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…Leakage may occur through fractures, faults or, more generally, caprock weaknesses which may act as preferential ascent routes for deep-seated gases (Ennis-King and Paterson, 2000, Pruess and Garcia, 2002, Rutqvist and Tsang, 2002. Experimental, modelling and field studies evaluating structural integrity of geological carbon repositories have been already conducted (see, among others, Li et al, 2006, Kaszuba et al, 2003, 2005, Gaus et al, 2005, Haszeldine et al, 2005, May, 2005, Marschall et al, 2005, Hildebrand et al, 2004, Pruess and Garcia, 2002, Rutqvist and Tsang, 2002, Ennis-King and Paterson, 2000, Lindeberg, 1997, and references cited therein). From these studies, the following key issues can be identified, which need to be addressed for a quantitative assessment of the sealing efficiency of caprock formations:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leakage may occur through fractures, faults or, more generally, caprock weaknesses which may act as preferential ascent routes for deep-seated gases (Ennis-King and Paterson, 2000, Pruess and Garcia, 2002, Rutqvist and Tsang, 2002. Experimental, modelling and field studies evaluating structural integrity of geological carbon repositories have been already conducted (see, among others, Li et al, 2006, Kaszuba et al, 2003, 2005, Gaus et al, 2005, Haszeldine et al, 2005, May, 2005, Marschall et al, 2005, Hildebrand et al, 2004, Pruess and Garcia, 2002, Rutqvist and Tsang, 2002, Ennis-King and Paterson, 2000, Lindeberg, 1997, and references cited therein). From these studies, the following key issues can be identified, which need to be addressed for a quantitative assessment of the sealing efficiency of caprock formations:…”
Section: Introductionmentioning
confidence: 99%
“…Dissolution reactions are likely when gas breakthrough is expected in carbonate-rich rocks, with both the type and timing of the mineralogical alteration in caprocks being highly variable and specific to geochemical, physical and hydrologic features of the investigated systems; (iii) the sealing capacity of caprock formations above depleted oil and/or gas reservoirs can be significantly reduced after CO 2 injection, due to the lower interfacial tension of the CO 2 -water system in comparison to hydrocarbon-water system originally filling the reservoir before the displacement operated by the injected CO 2 (Li et al, 2006); (iv) experimental data on capillary displacement pressure and effective permeability-capillary pressure relationships indicate that dynamic leakage of gases through the caprock depends on ambient pressure conditions; differences in gas breakthrough behaviour of gases are governed by interfacial tension and wettability behaviour of different gases which are specific to different lithologies (Hildebrand et al, 2004); (v) natural analogues provide useful information on geochemical processes occurring in natural environments that laboratory experiments may not be able to reproduce. Such information can assist in the calibration of geochemical models, allowing them to make accurate predictions at the timescales involved in nature (Haszeldine et al, 2005). This paper is focused on the study of the reactive mechanisms which may occur as a consequence of CO 2 geological disposal at depth in a potentially highly-reactive caprock, consisting of carbonate-rich shales.…”
Section: Introductionmentioning
confidence: 99%
“…This heterogeneity is site-dependent and scaledependent. Different sites may have different lithology (shale, mudstone, and claystone) and mineralogy (Haszeldine et al, 2005;Lu et al, 2009). The behavior of a clay-rich shale can be highly different from a carbonate-rich shale (Alemu et al, 2011).…”
Section: Field Observationmentioning
confidence: 99%
“…Natural analogues provide useful information on geochemical processes occurring in natural environments that laboratory experiments may not be able to reproduce. Such information can assist in the calibration of geochemical models, allowing them to make accurate predictions at the timescales involved in nature (Haszeldine et al, 2005).…”
Section: Discussionmentioning
confidence: 99%